Detection of airgap eccentricity using line current spectrum of induction motors - Guldemir, H (Elsevier Science Sa, 2003)
In this study, the machine with offset (eccentric) rotor has been studied. This study is of interest because rotor eccentricity can result in large forces applied to the rotor as well as some force harmonics with the potential to produce noise and vibrations. The current spectrum analysis is an accepted strategy for the monitoring and detection of airgap eccentricity in induction machines. M.m.f.-permeance wave approach has been used for simulating the machine under healthy and eccentric rotor conditions. A specially constructed eccentricity producing mechanism has been used to introduce static eccentricity by controlling the movement of the rotor core. The theoretical results have been compared with the experimental results. The simulation results are in close agreement with the experimental results. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: eccentric airgap; condition monitoring; eccentricity; current spectrum